Är företag inom Västra Götalandsregionen villiga att satsa på en infrastruktur via vattenvägar? - En studie kring utvecklingen av inlandssjöfart - Delemark, Mattias; Marmheden, Niklas (My University, 2017)
This bachelor thesis is based on the business industry and its view on inland waterways as a part of the infrastructure within the region of Västra Götaland (hereinafter referred to as VGR). When it comes to transporting goods within national boarders, inland shipping in Sweden is used to a much lesser extent compared to both road and railway. There are countries in central Europe that use inland waterways as a complement to additional infrastructure with seemingly good results. In order to handle the constant increase of general transportation of goods on a global level, Sweden is required to use all available resources in an efficient way connected to every means of inland transportation. Therefore, it is interesting to research whether or not there exists a genuine interest among the local companies in using a functioning inland shipping network for transportation along river Göta Älv and Lake Vänern. In line with this, investigating what the industry’s point of view is concerning the usage of inland shipping as a part of the logistical network, as well as what practical arrangements the region itself would have to solve in order to commit the companies to future investments is also a matter of interest. Through a case study with in-person semi structured interviews, the authors of this report examined different companies’ interest and commitment regarding the development of inland shipping. Furthermore, through an interview with Kristina Jonäng who is a representative for the political party "Centerpartiet" in VGR, the approach from the region of Västra Götaland concerning this means of transportation and its future relevance was analysed. The result of the case study offers the conclusion that there is an almost exclusively positive approach towards the usage of inland shipping among the interviewed companies. The major obstacle mentioned was connected to an inadequate infrastructure and increased lead time. However, an extensive majority of the respondents would consider using inland waterways if it was a fully functional alternative for transporting goods. A large number of companies also mentioned that through an extended use of inland shipping, this could help in reaching internally set environmental goals.
Keywords: Transport; Transportteknik och logistik; Transport; Transport Systems and Logistics